METHODOLOGY OF MANAGEMENT OF RIVER BASINS GEOCHEMICAL BALANCE IN WESTERN SIBERIA - Oleg G. Savichev; Natalya V. Guseva (Известия Томского политехнического университета: Инжиниринг георесурсов, 2020)
Relevance of the research is determined by a plenty of unresolved issues on estimation of water bodies condition and their long-term forecast, normalization of anthropogenous influences, sewage treatment and restoration of water bodies. The aim of the research istodevelop a methodology for management of geochemical balance of water ecological systems inWestern Siberia in various natural and anthropogenous conditions. Methods: landscape and geochemical, geographical and hydrological, statistical methods, methods of mathematical modelling of a water flow and chemical composition of waters. Results and conclusions. The authors have proposed the methodology of management ofriver basin geochemical balance. It consists in: 1) estimation of of water bodies condition, tendencies of its change and anthropogenous influence; 2) construction of a complex of mathematical models describing water runoff formation and chemical composition of waters; 3) development of the actions, which allow minimizing anthropogenous influence on water bodies; 4) estimation of water-security actions efficiency by comparison of results of observations and simulating. The authors developed the algorithm for defining the elements of geochemical balance of river basins and characterized the orientation of geochemical processes in water bodies inWestern Siberia. The key aspects of a choice of methods of sewage treatment and restoration of the broken areas are formulated. It is shown that construction of treatment facilities isreasonable if dump of the crude sewage makes more than 5 % from a runoff in closing section. The optimum structure of sewage treatment assumes wide use of sediment basins and constructions of biological clearing with natural aeration which are desirable for combining with natural downturn of a relief in river valleys or inside bogs for condition of engineering protection of territory. Restoration can be considered effective if the difference between values of elements of balance before infringement and after restoration does not exceed 20 %.